The missing half : a novel - Flowers, Ashley; Kiester, Alex (Bantam, 2025)
"Nicole "Nic" Monroe is in a rut. At twenty-four, she lives alone in a dinky apartment in her hometown of Mishawaka, Indiana, she's just gotten a DWI, and she works the same dead-end job she's been working since high school, a job she only has because her boss is a family friend and feels sorry for her. Everyone has felt sorry for her for the last seven years--since the day her older sister, Kasey, vanished without a trace. On the night Kasey went missing, her car was found over a hundred miles from home. The driver's door was open and her purse was untouched in the seat next to it. The only real clue in her disappearance was Jules Connor, another young woman from the same area who disappeared in the same way, two weeks earlier. But with so little for the police to go on, both cases eventually went cold. Nic wants nothing more than to move on from her sister's disappearance and the state it's left her in. But then one day, Jules's sister, Jenna Connor, walks into Nic's life and offers her something she hasn't felt in a long time: hope. What follows is a gripping tale of two sisters who will do anything to find their missing halves, even if it means destroying everything they've ever known"--